Posttherapeutic Critical Organ Dosimetry of Extensive 177Lu-PSMA Inhibitor Therapy With Metastatic Castration-Resistant Prostate Cancer One Center Results - Ozkan, Ahu; Ucar, Burcu; Seymen, Huelya; Yarar, Yasemin Yildiz; Falay, Fikri Okan; Demirkol, Mehmet Onur (LIPPINCOTT WILLIAMS & WILKINS, 2020)
Purpose Lu-177-PSMA inhibitor peptide receptor radioligand therapy (RLT) is playing an increasing role in metastatic castration-resistant prostate cancer. We aimed to estimate the absorbed radiation doses for critical organs (eg, kidneys, parotid glands, submandibular glands, and lacrimal glands) of patients treated with 4 to 6 cycles by Lu-177-PSMA inhibitor RLT, retrospectively, and to evaluate the findings extensively in order to determine the critical organ radiation-absorbed limitations and the number of prospective RLT. Materials and Methods A total of 51 cycles Lu-177-PSMA inhibitor RLT in 10 patients was analyzed. Therapies have been applied in 4 to 6 cycles with 8 to 10 weeks' intervals. Dosimetric estimates of kidneys, parotid glands, submandibular glands, and lacrimal glands have been calculated based on MIRD scheme pamphlet no. 16. Regions of interest were drawn with GE Xeleris Functional Imaging Workstation. OLINDA/EXM 1.1 simulation software was used to calculate radiation-absorbed doses. Results Mean radiation-absorbed doses were 0.70 +/- 0.24 Gy/GBq for kidneys, 1.34 +/- 0.78 Gy/GBq for parotid glands, 0.94 +/- 0.45 Gy/GBq for submandibular glands, and 2.28 +/- 1.29 Gy/GBq for lacrimal glands. Conclusions Due to the critical target organ risks and the optimal therapy doses, patient-specific dosimetry is a deterministic factor in radionuclide therapy. Even when the absorbed kidney doses were above the ICRP critical dose limits in patients who had 4 to 6 cycles of therapy, mortality due to nephrotoxicity has not been observed. Mild increased tolerated radiation dose is acceptable for the patient groups with very low survival rate.
Keywords: PSMA; radionuclide dosimetry; Lu-177; mCRPC; RLT; RADIONUCLIDE THERAPY; RISK; Radiology, Nuclear Medicine & Medical Imaging